Menjembatani Kesenjangan Akses Internet: Studi Kasus Indonesia Dan Brunei Darussalam - Fathimatuzzahra, Rahma Nabila; Dompak, Timbul (LPPM Universitas Putera Batam, 2024)
Technology is fast advancing in the modern day, especially in the field of information systems. The internet is crucial in enabling worldwide connectivity and providing access to vital information, making it critical in daily activities across the globe. This study investigates the discrepancy in internet connectivity between Indonesia and Brunei Darussalam, two Southeast Asian nations that are encountering obstacles in attaining widespread online accessibility. Both nations face challenges with internet infrastructure, especially in rural and remote areas, despite their different geographical and economic conditions. This study seeks to illuminate the notable disparities in internet accessibility and the factors that contribute to them in these two countries, using a comparative analysis.